Pengaruh Intensitas Cahaya dan Nutrisi Terhadap Pertumbuhan Miselium Pleurotus ostreatus di Tangerang - Gervasius Harwin Wangrimen; Ferdian Ferdian; Meyta Valentine; Yashinta Budiyanti; Indah Juwita Sari (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
White oyster mushroom (Pleurotus ostreatus) is a type of beneficial mushroom, widely used for consumption, medicinal ingredients, as well as business-oriented cultivation. Nutrition and light intensity are two of the most influential factors for the growth of white oyster mushroom mycelium. Nutrients such as water used for rice cooking (traditionally called air leri) and glucose solution are thought to be potential sources of nutrients, but it is not known which nutrients are more suitable for the growth of white oyster mushroom mycelium. This research was conducted to find out the growth rate difference of white oyster mushroom mycelium produced by vary LED (Light-Emitting Diode) light intensity (sequentially 0 lux, 103 lux, 2x103 lux, 3x103 lux, and 4x103 lux ), air leri nutrition with a 1:1 dilution ratio, glucose solution with 1:3 ratio. Processed data showed that the growth rate of white oyster mushroom mycelium with air leri nutrition for 18 days is better than glucose solution, while low light intensity will affect the color to the growth rate of mycelium on the bag log medium.